Effectiveness of Otago Exercise Program on Balance and Fear of Falling in the Eldery: A Systematic Literature - Arni Safara Ilmy; Mita Noviana (Jurnal Kesehatan Vokasional, 2025)
Background: Aging causes a decline in physiological functions that affect balance, increases the risk of falling, and triggers fear of falling in older adults. The Otago Exercise Program (OEP) is designed to improve balance and reduce fear of falling, although its effectiveness is still being studied.Objective: The study aims to evaluate the effectiveness of the OEP in improving balance and reducing fear of falling in older adults through a systematic literature review.Methods: This study used a systematic literature review method following the PRISMA guidelines and the PICO framework. Literature searches were conducted across six major databases using the keywords “Otago Exercise Program,” “balance,” “fear of falling,” and “older adults.” A total of 1,289 articles were identified, and 1,262 articles were screened after duplicates were removed. Of these, 1,245 articles were excluded for not meeting the inclusion criteria. Twelve articles were analyzed using the Critical Appraisal Skills Programme (CASP) 2024 instrument.Results: The 12 selected studies originated from various countries, including India, Switzerland, Greece, Turkey, Israel, China, Spain, Cyprus, and Iran. The results showed that the OEP consistently improved both static and dynamic balance. Additionally, most studies reported a significant reduction in fear of falling.Conclusion: OEP has been proven effective in improving balance and reducing fear of falling in the elderly. Further research with consistent duration and long-term monitoring is needed to enhance the generalizability of the results.